2021
DOI: 10.1002/trc2.12182
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from cilostazol to OPC‐13015 linked to mitigation of cognitive impairment

Abstract: Introduction Cilostazol may be a novel therapeutic agent for Alzheimer's disease. Its metabolite, OPC‐13015, has a stronger inhibitory effect on type 3 phosphodiesterase than cilostazol. Methods We prospectively enrolled patients with mild cognitive impairment to whom cilostazol was newly prescribed. Patients underwent the Montreal Cognitive Assessment (MoCA) twice, at a 6‐month interval. Plasma cilostazol, OPC‐13015, OPC‐13213, and OPC‐13217 concentrations were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Selecting the MMSE as the primary end point was mainly due to the lack of clinical studies using assessments other than the MMSE to evaluate cilostazol’s association with cognition when the present study was initially planned. However, a recent study by some of us reported that transitioning from cilostazol to 3,4-dehydrocilostazol was associated with preserving cognitive function, as evaluated by the Montreal Cognitive Assessment. Mild cognitive impairment is a complex condition encompassing various pathological factors, including vascular diseases; therefore, neuropsychological tests more sensitive to information-processing speed and executive function may be needed in future trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selecting the MMSE as the primary end point was mainly due to the lack of clinical studies using assessments other than the MMSE to evaluate cilostazol’s association with cognition when the present study was initially planned. However, a recent study by some of us reported that transitioning from cilostazol to 3,4-dehydrocilostazol was associated with preserving cognitive function, as evaluated by the Montreal Cognitive Assessment. Mild cognitive impairment is a complex condition encompassing various pathological factors, including vascular diseases; therefore, neuropsychological tests more sensitive to information-processing speed and executive function may be needed in future trials.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that cilostazol may be effective for treating patients with dementia. Several studies have examined the beneficial effects of cilostazol on cognitive impairment, but the results are inconsistent . To our knowledge, clinical trials specifically targeting patients with neurocognitive disorders who do not have a history of stroke have yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotyping of RNF213 p.R4810K was performed using a fully automated gene analysis system (GTS-7000; Shimadzu Corporation, Kyoto, Japan or LightCycler 96 system; Roche, Basel, Switzerland). These systems allow the direct detection of single-nucleotide polymorphisms from 1 µL of whole blood samples using real-time polymerase chain reaction 15) . The primer sequences used in the current analysis were 5'-TTCCAGAACGTCCAGCAAGT-3' (forward) and 5'-ACAGTCCTGGTCCTGTCAGA-3'…”
Section: Rnf213 Genotyping Examinationmentioning
confidence: 99%